Emerging technologies for food safety: A venture funding perspective - Readnour, R.S. (International Livestock Research Institute, 2021)
Presented by Robin S. Readnour, Mountain Group Partners, Tennessee, USA, at the Safe Food, Fair Food for Cambodia project closing workshop on 21–22 June 2021. Venture Funding is a private equity investment where investors provide capital to start-up (high risk) companies that they believe have high potential for return to investment. This model has proved successful in advancing technology which is otherwise deemed too risky to develop by other funding methods. Mountain Group Partners is a venture firm in Nashville Tennessee which invests in human and animal health biotech. Food safety is an investment area of focus for Mountain Group Partners. Mountain Group Partners looks at technology solutions for food safety in biosecurity, diagnostics, vaccines, and nutritional supplements. We discuss these technology areas and provide examples of companies with technologies that could apply to food safety solutions.